Зниження енергоємності процесу екскавації роторним екскаватором - Makarov V.M.; Griffen A.L.; Karpenko A.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2003)
The results of cross scheme application for coalface disintegration with rotary excavator ERP-2500 for brown coal production are presented. Power consumption of excavation process has been reduced by 40%, consumption of dipper teeth - by 12% and the grade of coal quality has been increased by 26%.